Institutional Investors Trading Strategy In Indonesia’s Government Bond Market During The 2008 Crisis - Gusdinar , Isabelle Aranditha; Koesrindartoto, Deddy Priatmodjo (Asian Academy of Management (AAM), 2014)
The importance of government bonds in covering shortages in a government’s budget is inseparable from the market players’ role in the government bond market. In this study, we examine whether institutional investors’ behaviour had causal effects on the government bond market index from April 2008 to April 2009. Moreover, we also observe whether foreign, bank, non-bank and central bank investors exhibit similar strategies in their bond trading activities. Granger causality tests and a Vector Error Correction Model (VECM) methodology have indicated that foreign investors become market leaders and tend to hold long-tenor bonds during crises to maintain an optimal level of risk in their portfolio. This also shows that foreign investors tend to hold the fall of index. Another result shows that both foreign and non-bank investors become market leaders who influence the bond market index and have similar trading strategies in the aftercrisis period. Meanwhile, the central banks become foreign investors’ and non-bank investors’ trade counterparts to provide liquidity and stabilise the bond price. Moreover, the results indicate that bank investors become the market makers in the bond market.